Quantificação de risco de piping em barragens de terra via abordagens probabilística e fuzzy - Gomes, Francisco Hiago de Siqueira (2019)
Piping has been constituted, around the world, as one of the main types of faults in earth dams, that can take them to collapse, if no preventive measures are taken. In the dam safetybrazilian legislation, dams should be classified by risk categories, whit piping occurrence is one of the critereas of classification, performed by means of a field inspection, whose results depends on the technicians expertise to identify and measure theanomalies manifested, being, therefore, a subjective process which carries a significant degree of uncertainty. That work aims to propose two quantitative methodologies for definition of piping risk in earth dams, one produced by a probabilistic approach and other produced by a fuzzy approach.The methodologies were developed to calculate the risk of piping occurrence allowing the attenuation of the inconsistencies and inaccuracies (uncertainties) in the parameters acquisition.The probabilistic approach is based on geotechnical, hydrological and time criteria, excluding from the analysis the structural deterioration of the dam, data with inherent uncertainties of acquisition, leaning to have a subjective evaluation by the technician responsible for the field inspection. In contrast, in the fuzzy model, which considers the structural deterioration of the dam, the uncertainties are relevant aspects in the analysis.In the Mamdani controller developed, subjectivity is inserted in all levels, with fuzzy sets, which integrate the linguistic variables of the model (age of the dam, susceptibility of soils to the piping occurrence, percentage of accumulation of water in the reservoir and level of deterioration of the dam), being responsible for the dilution of subjectivity and the other inherent uncertainties in each criteria considered in the model. For the model development were used the Cipoada dam, the Itaúna dam, the Jaburu I dam, the Martinopole dam and the Quandu dam, all located in Ceara state, Brazil. The results obtained allow the hierarchization of the intervention priorities, the monitoring of the piping risk evolution and support the proposition of an appropriate intervention protocol for the different levels of calculated piping risk.